Hematuria after COVID-19 infection - Momeñe-Rojas, Natalia Ane (2023)
We present the case of a 17-year-old male with fever, respiratory symptoms, pulmonary infiltrates on chest X-ray and intermittent macroscopic hematuria. After appropriate workup, the patient was diagnosed with recent COVID-19 infection with possible bacterial superinfection and postinfectious hematuria, probable secondary IgA nephropathy.